2012
DOI: 10.1161/circheartfailure.111.962951
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Continuous-Flow Left Ventricular Assist Devices as Destination Therapy

Abstract: Background-Continuous-flow left ventricular assist devices (LVADs) have become the dominant devices for mechanical circulatory support, but their cost-effectiveness is undetermined. This study assessed the cost-effectiveness of continuous-flow devices for destination therapy versus optimal medical management in advanced heart failure and compared the results with previous estimates for pulsatile devices. Methods and Results-A Markov model was developed to assess cost-effectiveness. Survival, hospitalization ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 22 publications
2
96
2
4
Order By: Relevance
“…Broader cost and resource-utilization issues also affect clinical care delivery to these patients. 24 Furthermore, understanding hospital patterns and trends toward readmission might help us answer an important underlying question: does implanting an LVAD into a patient who already has a complex, multimorbid condition make that patient less likely to need repeated hospitalizations? Clearly, LVAD therapy improves survival rates and the quality of life; the question is whether or not-by improving cardiac output-LVAD therapy can ultimately simplify the care of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Broader cost and resource-utilization issues also affect clinical care delivery to these patients. 24 Furthermore, understanding hospital patterns and trends toward readmission might help us answer an important underlying question: does implanting an LVAD into a patient who already has a complex, multimorbid condition make that patient less likely to need repeated hospitalizations? Clearly, LVAD therapy improves survival rates and the quality of life; the question is whether or not-by improving cardiac output-LVAD therapy can ultimately simplify the care of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was close to the Netherland's ICER (€107 600–€112 000/QALY) 11, 27. However, French ICER was significantly lower than published estimates coming from the USA 14, 15. Obviously, the USA has a less parsimonious approach than France, with healthcare expenditure per capita in 2014 almost twice the French level.…”
Section: Discussionmentioning
confidence: 74%
“…Economic evaluations of first‐generation and second‐generation LVADs showed that the ratio of incremental costs vs. incremental benefits is still relatively high, ranging from £53 527 ($84 963)/quality‐adjusted life year (QALY) in the UK to $201 600/QALY in the USA 8, 11, 14, 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In the United States, a general rule is that ICERs under $50,000 per QALY are considered cost-effective, while $50,000-$100,000 per QALY (perhaps as high as $200,000 for a continuous flow left ventricular assist device as destination therapy in patients with heart failure) is a gray area. 7 How do you evaluate the quality of cost-effectiveness studies? Good research practices for cost-effectiveness studies are available from an internationally recognized joint task force (see reference 8 for the Web link).…”
Section: How Is the Value Of A New Treatment Technology Or Practicementioning
confidence: 99%